Creative economy development strategy through communication in the alternative tourism of concert - Aulia, Sisca; Paramita, Sinta; Farid, Farid (Universitas Padjadjaran, 2025)
Background: As COVID-19 subsides, the government is working to rebuild the collapsed economic foundations. One area of focus is the development of the music industry in Indonesia. In 2023, concerts in Indonesia began to reemerge at the national and international levels. The Dewa 19 concert at the Jakarta International Stadium (JIS) and the Blackpink concert at the Gelora Bung Karno Main Stadium attracted a lot of attention. These concerts boosted the economy in several sectors, including alternative tourism. This study aims to explore the supporting components of alternative tourism through concerts and the strategic role of communication in developing the creative economy. Method: This study used a quantitative descriptive method. Results: The music industry in Indonesia has experienced a resurgence, with events such as The 90s Festival and international concerts, the Blackpink’s Born Pink World Tour. These music festivals increase tourism, providing economic opportunities for businesses and local communities. Blackpink’s concert in Jakarta is a prime example of how concerts can create economic value and social excitement. In addition, international concerts enhance Indonesia’s global image and reputation, and demonstrate the country’s ability to organize large-scale events. Conclusion: The rise of the Indonesian music industry and the impact of international concerts demonstrate the diverse cultural and economic dimensions of music in Indonesia and its ability to adapt, evolve, and thrive in the modern era.